PENERAPAN METODE TALKING STICK UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN HASIL BELAJAR KOGNITIF SISWA - Neni Rinjani; Agus Muliadi; Ida Royani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
This study aims to determine the level of communication skills and cognitive learning outcomes of students who are taught through talking stick learning models. This research was carried out at Darul Hikmah Middle School, Pagutan Village, Mataram District, Mataram City in the academic year 2018/2019. This type of research is a PTK with a Cycle I and II research design. Design sampling is done randomly. The research sample is class VIII. Data communication results and cognitive learning outcomes, obtained using communication questionnaires and multiple choice tests. Research instruments in the form of questionnaires and tests of student learning outcomes. The results of the study of the level of communication skills of students in the first cycle obtained a classical percentage, namely: 1) 5% (always); 2) 20% (often); and 3) 75% (sometimes). Whereas in the second cycle the classical percentage is obtained, namely: 1) 5% (always); 2) 60% (often); and 3) 35% (sometimes). In the cognitive learning outcomes of students, there are significant differences with students who are taught through the talking stick method, in the first cycle the classical percentage is 55%, and the second cycle is 85% classical percentage. Based on the data obtained, it shows that there is an increase of 30%. Based on the results of data analysis, it can be concluded that through the application of the talking stick method in integrated science learning can improve communication skills and cognitive learning outcomes of eighth grade students at Darul Hikmah Middle School. This is because the talking stick method can invite students to play an active role and involve all the abilities of students they have.